ظاهرة تأخر الزواج في المجتمع الماليزي المسلم وعلاجها : دراسة تحليلية في ضوء السنة النبوة - Qurrotul Aien Fatah Yasin (Kulliyyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2010)
The phenomenon of late marriage among Malaysian Muslim youth, male or female, is increasingly on the rise leading to various problems in Malaysian Muslim society. This thesis is aimed at studying this phenomenon with a view to investigating into main reasons for the late marriage and identifying possible solutions in the light of sunnah concerning the issue of marriage. This study is composed of three dimensions: (1) explanation of factors and impacts of late marriage in Malaysian Muslim society, (2) analysis of scholars' views on the issue and the society's reactions to the problem, and (3) search for solution to the problem in the light of Prophetic traditions and guidance as available in the compendia of Hadith. The conclusion reached at in the research is that the largest factors contributing to the late marriage are different between male and female: (1) the largest factor for male is financial difficulty, (2) the largest factor for female is problem in identifying suitable person for marriage, (3) preference to live independently, and others. The study has attempted to provide ample evidence that negative effects of late marriage in Malaysian society are outstripping its positive impacts, and offered preventive measures to the problem in the light of Prophetic traditions, suggesting that Malaysian Muslim society may save itself from further damages by acting upon the advises of the Last Prophet (s.a.w.). The methodology applied in this study is analytical.